KOORDINASI PELAKSANAAN PROGRAM KARTU TANDA PENDUDUK ELEKTRONIK DI KECAMATAN PUTUSSIBAU UTARA KABUPATEN KAPUAS HULU - A.A. Berry Febriardi E.42009041 (FISIP Universitas Tanjungpura Pontianak, 2021)
The writing of this script intended to find out and analyze the process of coordination refers to Henry Fayol’s Coordination Theory in the implementation of Electronic Identity Card in the District of North Putussibau specially about the special treatment for elderly people because of no duty explanation for the team, the lack of active role of program’s coordinator and public awareness about the important of population administration. This study used the perspective of qualitative research methods and observation, interview and documentation technique in data collection.The conclusion of this study are there needs to be the duty explanations for the team about special treatment for the elder people in the electric identity card program, the coordinator active roles during program implementation, and peoples awareness improvement about population administration so that the program implementation can be more organized and effective. Keywords : coordination, attachment, unity, aligned, Electronic Identity Card